Operative Treatment of Elbow Injuries - Baker, Champ L.; Plancher, Kevin D. (Springer New York, 2002)
Operative Treatment of Elbow Injuries is a complete presentation of all surgical approaches to repair of the elbow, and will demonstrate the most effective management of elbow injuries and problems. The book brings together a prestigious group of leaders in the field, who share their expertise and experiences to present the full scope of every aspect of elbow procedures. Discussions focus on clinical anatomy, physical exam, nonoperative treatment, indications, contraindications, operative techniques, results and expectations, and complications. This volume features information on arthroscopy of the elbow, soft tissue injuries, compression syndromes, and the "hot" new techniques of distraction arthroplasty, as well as distraction devices for contracture release. Sports-related injuries, as well as treatment of children's elbow injuries, are addressed extensively. Enhanced with over 450 specially prepared illustrations, this book will be extremely useful to the orthopaedic surgeon and the sports medicine specialist.